The impact of affirmative action on the employment of minorities and women over three decades: 1973-2003 - Fidan Ana Kurtulus (W.E. Upjohn Institute for Employment Research, 2015)
What role has affirmative action played in the growth of minority and female employment in U.S. firms? This paper analyzes this issue by comparing the employment of minorities and women at firms holding federal contracts and therefore mandated to implement affirmative action, and at noncontracting firms, over the course of three decades spanning 1973-2003. It constitutes the first study to comprehensively document the long-term impact of affirmative action in federal contracting on the U.S. employment landscape. The study uses a new panel data set of over 100,000 large private-sector firms across all industries and regions, obtained from the U.S. Equal Employment Opportunity Commission, and it exploits rich variation across firms in the timing of federal contracting to identify affirmative action effects. The paper's key results indicate that the primary beneficiaries of affirmative action in federal contracting over 1973-2003 were black and Native American women and men. Analysis of the dynamics of workforce composition around the time of contracting reveals that a large part of the effect of affirmative action on increasing protected group shares occurred within the first four years of gaining a contract, and that these increased shares persisted even after a firm was no longer a federal contractor. The paper also uncovers important results on how the impact of affirmative action evolved over 1973-2003. In particular, it finds that the fastest growth in the employment shares of minorities and women at federal contractors relative to noncontracting firms occurred during the 1970s and early 1980s, decelerating substantially in ensuing years.
Keywords: J15; J16; J21; J7; K31; N32; N42; M51; 330; Affirmative Action in the Labor Market; Gender; Race; Workforce Composition